Core-shell meso-beta@mesoporous aluminosilicate supported Ni2P catalyst for the hydrodenitrogenation of quinoline: Effect of core shell structure on Ni2P particle size. (15th October 2021) - Gong, Hanzhang; Xiao, Zhiwei; Zhuang, Yuan; Liang, Shuqin; Li, Xiang; Zheng, Weibo; Duan, Aijun; Zhang, Xiao; Liu, Jian
Highlights: Meso-beta@MAS was controllably synthesized through a combination of alkali treatment with self-assembly. The meso-beta core can provide suitable acidity and the microporous framework can anchor Ni2 P particles. The open wormlike pore structure of MAS shell can make more reactants contact with the Ni2 P active species. The interface of the core–shell structure makes Ni2+ interact more strongly with the support. Ni2 P/meso-beta@MAS core–shell catalyst exhibits high quinoline hydrogenation activity. Abstract: A core–shell structured material with a mesoporous aluminosilicate (MAS) shell and mesopore-containing beta zeolite (meso-beta) core was synthesized by self-assembly using triblock copolymer (P123) as template. The corresponding Ni2 P catalyst for quinoline hydrodenitrogenation (HDN) was prepared by the hypophosphite disproportionation method. The core–shell support exhibits a wide pore structure, large surface area, suitable amounts of Lewis and Bronsted acid sites, and a large number of acidic hydroxyl groups exist at the interface of MAS and meso-beta. These properties contribute to the formation of very small (4.7 nm) Ni2 P clusters. Furthermore, the micropores of the zeolite core can anchor the Ni2 P nanoparticles and prevent nanoparticle aggregation. The smaller Ni2 P particle size can expose more active sites and thus results in higher catalytic activity. The obtained Ni2 P/meso-beta@MAS catalyst exhibits a higher reaction rate constant and TOF (12.37 × 10 -2 μmolg −1 s −1 and 1.7 × 10 −3 s −1, respectively) for the quinoline HDN reaction compared to a silica-supported Ni2 P catalyst (6.18 × 10 −2 μmolg −1 s −1 and 1.5 × 10 −3 s −1, respectively) and Ni2 P/H-beta catalyst (6.81 × 10 −2 μmolg −1 s −1 and 1.4 × 10 −3 s −1, respectively).